Pre-hospital care metrics as reflected in lebanese red cross ambulance response data, fourth quarter, 2016 - Srour, F. Jordan (2018)
This document reports data from the Lebanese red Cross regarding calls received for ambulance services in 2016. The primary aim of this report is to illustrate facets of the pre-hospital care system in Lebanon via data analysis. As the Lebanese Red Cross operates throughout Lebanon, analysis of their ambulance response data allows for a broad picture regarding how the Lebanese population uses ambulance services and what impact system structures (eg. roadway dynamics and hospital locations) have on pre-hospital care.